Learning and consolidation of visuo-motor adaptation in Parkinson's disease - Marinelli, Lucio; Crupi, Domenica; Di Rocco, Alessandro; Bove, Marco; Eidelberg, David; Abbruzzese, Giovanni; Ghilardi, M. Felice (Parkinsonism & related disorders, 2009)
We have previously shown in normal subjects that motor adaptation to imposed visual rotation is significantly enhanced when tested few days later. This occurs through a process of sleep-dependent memory consolidation. Here we ascertained whether patients with Parkinson's disease (PD) learn, improve, and retain new motor skills in the same way as normal subjects. We tested 16 patients in early stages of PD and 21 control subjects over two days. All subjects performed reaching movements on a digitizing tablet. Vision of the limb was precluded with an opaque screen; hand paths were shown on the screen with the targets' position. Unbeknownst to the subjects, the hand path on the screen was rotated by 30°. In experiment 1, patients taking dopaminergic treatment and controls adapted to rotation with targets appearing in an unpredictable order. In experiment 2, drug-naïve patients and controls adapted to rotation in a less challenging task where target's appearance was predictable. Patients and controls made similar movements and adapted to rotation in the same way. However, when tested again over the following days, controls' performance significantly improved compared to training, while patients' performance did not. This lack of consolidation, which is present in the early stages of the disease and is independent from therapy, may be due to abnormal homeostatic processes that occur during sleep.